1972
DOI: 10.4039/ent104145-2
|View full text |Cite
|
Sign up to set email alerts
|

The Temporary Abatement of Nuisance Species of Trichoptera With DDD (Tde) Larvicide

Abstract: Can. Ent. 104: 145-163 (1972)Nuisance species of riverine insects were temporarily eliminated from the Expo 67 site at Montreal in 1967 by four applications of an emulsifiable formulation of DDD (TDE) to the St. Lawrence River, one in each of the months of May, June, July, and August of 1967. In each treatment sufficient DDD was applied 1.5 miles above the infested rapids to provide a concentration of about 0.4 p.p.m. of DDD in the water, throughout a period of about 15 minutes. Each treatment caused the immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Lack of time prevented testing additional chemicals. Partly because of these results, and partly because the effects of DDT and DDD in natural aquatic ecosystems, were better known than those of organophosphates, DDD was selected in 1966 for further tests in the St. Lawrence River to control the larvae of nuisance species of Trichoptera (Fredeen 1972). Several authors, reviewed in part by Fredeen (1972) have shown that residues of DDD are considerably less persistent than those of DDT or DDE, and that furthermore DDD does not possess the harmful estrogenic activity of DDE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of time prevented testing additional chemicals. Partly because of these results, and partly because the effects of DDT and DDD in natural aquatic ecosystems, were better known than those of organophosphates, DDD was selected in 1966 for further tests in the St. Lawrence River to control the larvae of nuisance species of Trichoptera (Fredeen 1972). Several authors, reviewed in part by Fredeen (1972) have shown that residues of DDD are considerably less persistent than those of DDT or DDE, and that furthermore DDD does not possess the harmful estrogenic activity of DDE.…”
Section: Discussionmentioning
confidence: 99%
“…In 1965 and 1966 during the early stages of the Expo 67 Shadily Project at Montreal (Fredeen 1969) there was need to evaluate the effects of insecticides on the larvae of several nuisance species of Trichoptera that occurred in enormous June 1972 numbers in rapids of the St. Lawrence River. This is a report of the methods used and results from tests with three species.…”
Section: Introductionmentioning
confidence: 99%
“…In other areas and under other conditions, closely related species of these two genera have been recorded as occurring in such enormous numbers that they constitute a serious nuisance in the adult state, and thus become undesirable "target" organisms. At the time of EXPO 67, control of this nuisance could only be done by extensive larviciding of the St. Lawrence River (Fredeen 1972a and b)…”
Section: Resultsmentioning
confidence: 99%
“…The mass emergence of adult aquatic insects often causes a severe nuisance, such as disruption of business, poor visibility, traffic problems, and foul odor (Munroe 1951;Peterson 1952;Osgood 1957;Fredeen 1972). Furthermore, Parlato (1929) identified the hairy wing of caddisfly as an inhalant allergen worldwide.…”
Section: Introductionmentioning
confidence: 99%